Cannabinoid receptor 2 plays a central role in renal tubular mitochondrial dysfunction and kidney ageing. Issue 18 (19th August 2021) - Zhou, Shan; Ling, Xian; Meng, Ping; Liang, Ye; Shen, Kunyu; Wu, Qinyu; Zhang, Yunfang; Chen, Qiyan; Chen, Shuangqin; Liu, Youhua; Zhou, Lili
Abstract: Kidney is one of the most important organs in maintaining the normal life activities. With the high abundance of mitochondria, renal tubular cell plays the vital role in functioning in the reabsorption and secretion of kidney. Reports have shown that mitochondrial dysfunction is of great importance to renal tubular cell senescence and subsequent kidney ageing. However, the underlying mechanisms are not elucidated. Cannabinoid receptor 2 is one of the two receptors responsible for the activation of endocannabinoid system. CB2 is primarily upregulated in renal tubular cells in chronic kidney diseases and mediates fibrogenesis. However, the role of CB2 in tubular mitochondrial dysfunction and kidney ageing has not been clarified. In this study, we found that CB2 was upregulated in kidneys in 24‐month‐old mice and d ‐galactose (d ‐gal)‐induced accelerated ageing mice, accompanied by the decrease in mitochondrial mass. Furthermore, gene deletion of CB2 in d ‐gal‐treated mice could greatly inhibit the activation of β‐catenin signalling and restore the mitochondrial integrity and Adenosine triphosphate (ATP) production. In CB2 knockout mice, renal tubular cell senescence and kidney fibrosis were also significantly inhibited. CB2 overexpression or activation by the agonist AM1241 could sufficiently induce the decrease in PGC‐1α and a variety of mitochondria‐related proteins and trigger cellular senescence in cultured human renal proximal tubular cells. CB2‐activated mitochondrial dysfunction and cellular senescence could be blocked by ICG‐001, a blocker for β‐catenin signalling. These results show CB2 plays a central role in renal tubular mitochondrial dysfunction and kidney ageing. The intrinsic mechanism may be related to its activation in β‐catenin signalling.